Os Fiagros, o capital fictício e a financeirização recente do agronegócio brasileiro / The Fiagros, the fictitious capital and the recent financialisation of brazilian agribusiness / Les Fiagros, le capital fictif et la financiarisation récente du agrobusiness au Brésil - Boechat, Cássio Arruda (REVISTA NERA, 2024)
This article takes a preliminary look at the constitution and recent performance of the Agricultural Chain Investment Funds, or Fiagros, created in 2021. It seeks to understand them as part of the unfolding of financial mechanisms created since the 1990s by the process of securitisation of Brazilian agribusiness debts. Theoretically, we analyse the current "inflation of financial assets" through the concept of "fictitious capital" and thus propose an understanding of the current phase of "financialisation" of agriculture and land in Brazil. In this way, we observe, through the Fiagros, a renewal of promises of valorisation of agricultural production interlaced with "debt circuits", pushing for the expansion of production and productivity in agriculture, often aggravating conflict in the countryside and reinforcing a critical characterisation of the reproduction of Brazilian agribusiness.